Identification of Diatoms in the Different Water Bodies of Gorakhpur - Kajol Bhati; Tanya Shree; Deepanshu Singh; Nikhil Khapra (Indian Journal of Forensic Medicine and Pathology, 2025)
In both forensic and medical-legal investigations, diatoms are an essential component of the evidence. The discovery of diatoms can shed light on whether the individual drowned before they passed away, or not. The purpose of this research was to determine which species of Diatom are present in the various bodies of water that are located in and around the Gorakhpur district of Uttar Pradesh, India. For the purpose of this study, water samples were gathered from three distinct categories of water bodies located in Gorakhpur. These categories include running rivers, still rivers, and drained rivers. The samples were stored in sterilized water bottles with tops that had a snug𿿿t. The procedure of Lugols iodine method s used o identify the diatoms from the water sample. Under a microscope with a camera in hand, each species of diatom is examined and photographed at the same time. 13 different diatom species were identi𿿿ed and their names are Pseudo-Nietzsche p, Epithemia sorex sp, Nitzschia linearis sp, Craticula sp, Bacillaria paxillifer sp, Cyclotella sp, Cembella sp., achnanthidium- minutissimum sp, Detonula sp, and many more sp. The results of this experiment will be useful in further research on diatoms, as well as in determining the locations of areas where crimes have been committed.